Srečanja med Hermesom in Afrodito - Zupančič, Metka (Primerjalna književnost, 2003)
Hermes and Aphrodite Encounters. Based on the assumption about the presence of ancient myths in contemporary literature, philosophy and culture, the article explores trends in recent analyses of mythical patterns, especially in myth criticism such as developed by Gilbert Durand. Two mythical patterns, those of Hermes and Aphrodite, appear prevalent in our times. The article highlights various approaches to these two myths and mentions various literary texts where they can be identified.
Keywords: Durand, Gilbert, 1921-; književnost; literature; literatura; miti; mythology; mitologija; antična mitologija; Hermes; Afrodita